Genetically predicted circulating levels of cytokines and the risk of osteoarthritis: A mendelian randomization study - Su, Dalin; Ai, Yanhong; Zhu, Guoyong; Yang, Yubiao; Ma, Pengyi (Frontiers in Genetics, 2023)
The association between inflammatory cytokines and osteoarthritis (OA) has been reported in several observational studies, but the causal relationship between the two remains unknown. Hence, we performed this two-sample Mendelian randomization (MR) to confirm the causal relationship between circulating levels of inflammatory factors and osteoarthritis risk. We used genetic variants associated with cytokine circulation levels from a meta-analysis of genome-wide association studies (GWASs) in 8,293 Finns as instrumental variables and obtain OA data from the UK Biobank, including a total of 345,169 subjects of European ancestry (66,031 diagnosed OA cases and 279,138 controls). Inverse variance weighting (IVW), MR-Egger, Wald Ratio, weighted median, and MR multiplicxity residual sums with outliers (MR-PRESSO) were used.We found a causal relationship between circulating levels of macrophage inflammatory protein-1beta (MIP-1) and risk of OA (OR=0.998, 95% CI=0.996-0.999, P=9.6110-5); tumor necrosis factor beta (TNF-) was also causally associated with risk of OA (OR= 0.996,95%CI=0.994-0.999, P=0.002); finally we found a suggestive association between C-C motif chemokine ligand 5(CCL5, also called Rantes) and OA risk (OR=1.013, 95%CI= 1.002-1.024, P=0.016). Our study systematically assessed the role of inflammatory cytokines among OA through a genetic epidemiological approach. It provides new insights into the pathogenesis of OA and also provides potential therapeutic targets for the treatment of OA.